Negative electrode hard carbon material, preparation method thereof, negative electrode composition, sodium ion secondary battery and use thereof
By doping a specific content of phosphorus elements into the negative electrode hard carbon material of sodium ion secondary batteries and controlling disordered parameters fa, the problem of insufficient performance of negative electrode materials in the prior art is solved, and significant capacity performance and first-time effect are achieved. Improved efficiency and cycling performance, while also having cost advantages.
Patent Information
- Application Number
- CN202311840962.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-28
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-12-28
AI Technical Summary
The negative hard carbon materials of existing sodium ion secondary batteries have shortcomings in capacity performance, first-time Coulomb efficiency and cycle performance, and it is difficult to meet the requirements of high-performance batteries.
By doping a specific content of phosphorus in the hard carbon material and controlling the disordered parameter fa in the range of 0.25≤fa≤0.75, a negative electrode hard carbon material with improved capacity performance, first Coulomb efficiency and cycling performance was prepared.
The comprehensive performance of sodium ion secondary batteries is significantly improved, including capacity performance, first-time Coulomb efficiency and cycling performance, and the raw materials used are cheap and have cost advantages.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention generally relates to the field of energy storage technology, in particular to the field of sodium ion secondary batteries. Specifically, the present invention relates to a negative electrode hard carbon material, a preparation method thereof, a negative electrode composition comprising the negative electrode hard carbon material, a sodium ion secondary battery comprising the negative electrode composition, and uses of the sodium ion secondary battery. Background Art
[0002] In recent years, secondary batteries have played an increasingly important role in people's production and life. Compared with lithium-ion secondary batteries, sodium-ion secondary batteries are favored by the industry because of their abundant sodium reserves, low prices, and many similarities with mature lithium-ion secondary batteries in terms of process routes. Similar to lithium-ion secondary batteries, sodium-ion secondary batteries generally include a positive electrode, a negative electrode, and a separator arranged between the positive electrode and the negative electrode, and work by repeated insertion, transfer, and transmission of sodium ions between the positive and negative electrodes. For the negative electrode of the secondary battery, carbon-based materials such as graphite are usually used as the negative electrode. However, the interlayer spacing of the graphite negative electrode is small, the sodium storage capacity is limited, and the rate performance is poor, which makes it difficult to meet the requirements of high-performance secondary batteries. For this reason, people have begun to turn their attention to non-graphite materials.
[0003] At present, the non-graphite negative electrode materials used in secondary batteries are mainly hard carbon and soft carbon. Among them, soft carbon has a high degree of graphitization and a small interlayer spacing. In contrast, hard carbon is difficult to graphitize and has a large interlayer spacing, so it has attracted people's attention. As a common non-graphite material, hard carbon does not have a long-range ordered structure. Some of its carbon layers are arranged randomly and stacked disorderly to form a large number of defects and holes. With the rapid development of the battery field, people have higher and higher requirements for battery performance such as capacity performance, first coulomb efficiency and cycle performance, which has prompted researchers to conduct extensive research on many aspects including hard carbon.
[0004] CN105453305A discloses a hard carbon material prepared using poly[(phenol glycidyl ether)-(co-formaldehyde)] and phosphoric acid, which exhibits high reversible capacity, high first coulombic efficiency and high rate characteristics. However, the process uses polymers as raw materials, which is costly.
[0005] CN114695894A discloses a high-capacity hard carbon fast-charge negative electrode material, which uses nitrogen-phosphorus-doped hard carbon as the core and metal oxides and amorphous carbon as the shell, thereby achieving good fast-charge performance, high energy density and first coulomb efficiency. However, the process preparation is relatively complicated.
[0006] CN113113601A discloses a phosphorus-doped hard carbon material, which uses phosphorus-doped hard carbon as the core and is coated with a polymer material as the outer layer to obtain the phosphorus-doped hard carbon material, and uses it in lithium-ion secondary batteries to obtain a higher specific capacity and first coulomb efficiency. However, the phosphorus-doped hard carbon material obtained by this process is doped with a higher content of phosphorus (the phosphorus doping amount is 0.3-5% by weight of the total weight of the phosphorus-doped hard carbon material), and the process uses a polymer as a raw material, which is more expensive.
[0007] Damien et al. (“A SAXS outlook on disordered carbonaceous materials for electrochemical energy storage”, Energy Storage Materials 21 (2019) 162-173) established a model to study the structure of hard carbon materials prepared from different precursors. They found that the disorder parameter f derived from small-angle X-ray scattering data a It can better reflect the disorder degree of hard carbon materials. However, Damien did not study the disorder parameter f a Impact on secondary battery performance.
[0008] In view of the current status of existing technologies, further research is still needed to provide hard carbon materials with better comprehensive performance, including capacity performance, first coulombic efficiency and cycle performance, so as to better meet market demand. Summary of the invention
[0009] The present invention is made in view of the above problems existing in the prior art.
[0010] In a first aspect, the present invention relates to a negative electrode hard carbon material for a sodium ion secondary battery, which satisfies:
[0011] The phosphorus content ranges from 0.001 wt % ≤ P ≤ 0.300 wt %, such as 0.005 wt % ≤ P ≤ 0.250 wt % or 0.010 wt % ≤ P ≤ 0.160 wt % or 0.010 wt % ≤ P ≤ 0.100 wt %, based on the total weight of the negative electrode hard carbon material; and
[0012] Unordered parameter f a The range is 0.25≤f a ≤0.75, for example 0.29≤f a ≤0.50 or 0.33≤f a ≤0.50 or 0.33≤f a ≤0.46, where f a Calculated by the following formula:
[0013]
[0014] in
[0015]
[0016]
[0017] Wherein d is the distance between two adjacent pores in the negative electrode hard carbon material. The average spacing of the calculation, ξ is the factor limiting the long-range orderly expansion. The correlation length, d and ξ are obtained by fitting the small angle X-ray scattering data of the negative electrode hard carbon material.
[0018] In a second aspect, the present invention relates to a method for preparing the negative electrode hard carbon material according to the first aspect of the present invention, comprising:
[0019] (1) treating a carbon source in an air atmosphere at a temperature of 60-300° C., for example, 80-280° C., for 1-24 hours, for example, 2-20 hours;
[0020] (2) adding a phosphorus source to the product obtained in step (1), and then treating the resulting mixture under an inert gas atmosphere at a temperature of 60-300° C., for example, 60-260° C., for 1-12 hours, for example, 2-10 hours;
[0021] (3) pre-carbonizing the product obtained in step (2) at a temperature of 400-650° C., for example, 400-600° C., for 0.5-12 hours, for example, 1-8 hours, under an inert gas atmosphere;
[0022] (4) repeatedly washing the product obtained in step (3) with deionized water until the pH of the product is in the range of 2.0-5.0, and optionally drying;
[0023] (5) uniformly mixing the product obtained in step (4) with at least one of sodium hydroxide, potassium hydroxide, sodium carbonate or potassium carbonate, sodium bicarbonate or potassium bicarbonate powder, and then sintering at a temperature of 500-900° C., such as 550-850° C., under an inert gas atmosphere for 0.5-12 hours, such as 2-10 hours; or
[0024] The product obtained in step (4) is stirred and soaked in at least one of sodium hydroxide, potassium hydroxide, sodium carbonate or potassium carbonate, sodium bicarbonate or potassium bicarbonate solution at a temperature of 20-100° C. for 1-12 hours, and then filtered to obtain a filter cake;
[0025] (6) repeatedly washing the product obtained in step (5) with deionized water until the pH of the product is in the range of 10.0-12.0;
[0026] (7) soaking the product obtained in step (6) in an acid solution at a temperature of 20-100° C. for 1-12 h with stirring, then filtering, and repeatedly washing the filter cake with deionized water until the pH value thereof is in the range of 2.0-5.0, and then drying;
[0027] (8) crushing the product obtained in step (7) to D v 50 particle size in the range of 1.0-20.0 μm; and
[0028] (9) The product obtained in step (8) is subjected to high temperature carbonization at a temperature of 1050-1600° C., for example, 1200-1500° C., for 2-8 hours, for example, 2-6 hours, under an inert gas atmosphere, and is optionally crushed.
[0029] In a third aspect, the present invention relates to a negative electrode composition, which is a negative electrode composition for a sodium ion secondary battery, comprising the negative electrode hard carbon material according to the first aspect of the present invention.
[0030] In a fourth aspect, the present invention relates to a sodium ion secondary battery, comprising the negative electrode composition according to the third aspect of the present invention.
[0031] In a fifth aspect, the present invention relates to the use of the sodium ion secondary battery of the fourth aspect of the present invention in an energy storage device for solar power generation, wind power generation, smart grid peak regulation, distributed power stations, backup power supplies or communication base stations.
[0032] The inventor unexpectedly discovered in the research that by doping a specific content of P element into the hard carbon material, the disorder parameter f of the hard carbon material can be adjusted at the same time. a Within a specific range, relative to P content and f a In the case of not being within the limited range, significantly improved comprehensive performance including capacity performance, first coulombic efficiency and cycle performance can be obtained. In addition, the raw materials used in the present invention are low in price and have cost advantages. DETAILED DESCRIPTION
[0033] In order to make the invention purpose, technical solution and beneficial technical effect of the present application clearer, the present application will be described in detail below. It should be noted that the various aspects, features, implementation methods and advantages described in the present application may be compatible and / or may be combined together.
[0034] Unless otherwise specified, the meanings of the technical terms in this specification are the same as those generally understood by those skilled in the art.
[0035] The present invention relates to a negative electrode hard carbon material, a preparation method thereof, a negative electrode composition comprising the negative electrode hard carbon material, a sodium ion secondary battery comprising the negative electrode composition, and use of the sodium ion secondary battery.
[0036] The present invention will be described in detail below.
[0037] Negative hard carbon material
[0038] In a first aspect, the present invention relates to a negative electrode hard carbon material for a sodium ion secondary battery, which satisfies:
[0039] The phosphorus content ranges from 0.001 wt % ≤ P ≤ 0.300 wt %, such as 0.005 wt % ≤ P ≤ 0.250 wt % or 0.010 wt % ≤ P ≤ 0.160 wt % or 0.010 wt % ≤ P ≤ 0.100 wt %, based on the total weight of the negative electrode hard carbon material; and
[0040] Unordered parameter f a The range is 0.25≤f a ≤0.75, for example 0.29≤f a ≤0.50 or 0.33≤f a ≤0.50 or 0.33≤f a ≤0.46, where f a Calculated by the following formula:
[0041]
[0042] in
[0043]
[0044]
[0045] Wherein d is the distance between two adjacent pores in the negative electrode hard carbon material. The average spacing of the calculation, ξ is the factor limiting the long-range orderly expansion. The correlation length, d and ξ are obtained by fitting the small angle X-ray scattering data of the negative electrode hard carbon material.
[0046] Unordered parameter f a It is a parameter proposed by Damien et al. when they established a model to study the structure of hard carbon materials made from different precursors. Damien found that this parameter can better reflect the degree of disorder of hard carbon materials. However, Damien did not study the influencing factors of this parameter and its impact on battery performance.
[0047] The inventors unexpectedly discovered in their research that when the disorder parameter f of the hard carbon material is adjusted aWithin a specific range, and when the P element content in the hard carbon material is controlled within a specific range at the same time, the comprehensive performance including capacity performance, first coulombic efficiency and cycle performance is significantly improved compared to the case where either of the two is not within the specified range of the present invention.
[0048] It should be noted that the inventors found in their research that the P content and the disorder parameter f a Affected by various factors such as the amount of added P source, pre-carbonization temperature, alkali treatment, high temperature carbonization temperature, etc., the above parameters can be comprehensively controlled to obtain the P content and f within the limited range of the present invention. a .
[0049] In the negative electrode hard carbon material of the present invention, the doping amount of the P element (i.e., the P element content in the final negative electrode hard carbon material) is 0.001 wt%≤P≤0.300 wt%, for example, 0.005 wt%≤P≤0.250 wt%, based on the total weight of the negative electrode hard carbon material. For example, based on the total weight of the negative electrode hard carbon material, the doping amount of the P element may be 0.001, 0.005, 0.010, 0.015, 0.020, 0.025, 0.030, 0.035, 0.040, 0.045, 0.050, 0.055, 0.060, 0.065, 0.070, 0.075, 0.080, 0.085, 0.090, 0.095, 0.100, 0.105, 0.110, 0.115, 0.120, 0.125, 0.130, 0.135, 0.140, 0.145 %, 0.150, 0.155, 0.160, 0.165, 0.170, 0.175, 0.180, 0.185, 0.190, 0.195, 0.200, 0.205, 0.210, 0.215, 0.220, 0.225, 0.230, 0.235, 0.240, 0.245, 0.250, 0.255, 0.260, 0.265, 0.270, 0.275, 0.280, 0.285, 0.290, 0.295, 0.300 wt %, or any two of them. For example, the doping amount of P element is 0.010 wt %≤P≤0.160 wt %, based on the total weight of the negative electrode hard carbon material. When the doping amount of the P element in the negative electrode hard carbon material is within the above range, further improved capacity performance and cycle performance can be obtained at the same time. For another example, the doping amount of the P element is 0.010 wt % ≤ P ≤ 0.100 wt %, based on the total weight of the negative electrode hard carbon material. When the doping amount of the P element in the negative electrode hard carbon material is within the above range, the cycle performance can be further improved.
[0050] In the negative electrode hard carbon material of the present invention, the disorder parameter f aThe range is 0.25≤f a ≤0.75. For example, the disorder parameter f a 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, or any two of them. When the disorder parameter f a In the above range, compared with f a When the value is not within the above range, it has improved first coulombic efficiency, capacity performance and cycle performance. For example, the disorder parameter f a The range is 0.29≤f a ≤0.50. When the disorder parameter f of the negative electrode hard carbon material a When it is within the above range, a good first coulombic efficiency can be obtained while further improving the capacity performance and cycle performance. a The range is 0.33≤f a ≤0.50. When the disorder parameter f of the negative electrode hard carbon material a When the disorder parameter f is within the above range, further improved cycle performance can be obtained. a The range is 0.33≤f a ≤0.46. When the disorder parameter f of the negative electrode hard carbon material a Within the above range, further improved capacity performance can be obtained.
[0051] In addition, further studies have found that when the negative electrode hard carbon material of the present invention meets one or more of the following conditions, further improved comprehensive performance can be obtained.
[0052] In some embodiments, the average pore diameter of the negative electrode hard carbon material of the present invention is 1.5-3.0 nm, such as 1.5-2.5 nm. As an example, the average pore diameter of the negative electrode hard carbon material can be 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0 nm, or any two thereof. aWhen the average pore diameter of the negative electrode hard carbon material is within the above range, the capacity performance and cycle performance can be further improved. For example, the average pore diameter of the negative electrode hard carbon material is 1.7-2.3nm. When the average pore diameter of the negative electrode hard carbon material is within the above range, the capacity performance and cycle performance can be further improved at the same time.
[0053] The average pore diameter R of the hard carbon material can be calculated by using the parameters d and ξ obtained by fitting the small-angle X-ray scattering data of the hard carbon material and substituting them into the following formula:
[0054]
[0055] in
[0056]
[0057] In some embodiments, the BET specific surface area of the negative electrode hard carbon material of the present invention is 1.0-35.0 m 2 / g, for example 3.0-35.0m 2 / g. As an example, the BET specific surface area of the negative electrode hard carbon material can be 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 16.0, 17.0, 18.0, 19.0, 20.0, 21.0, 22.0, 23.0, 24.0, 25.0, 26.0, 27.0, 28.0, 29.0, 30.0, 31.0, 32.0, 33.0, 34.0, 35.0 m 2 / g, or within the range defined by any two of them. a When the BET specific surface area of the negative electrode hard carbon material is within the above range, further improved capacity performance and cycle performance can be obtained. For example, the BET specific surface area of the negative electrode hard carbon material is 4.5-14.5 m 2 / g. When the BET specific surface area of the negative electrode hard carbon material is within the above range, further improved cycle performance can be obtained. The BET specific surface area of the hard carbon material can be measured by conventional measurement methods in the art, for example, it can be measured with reference to GB / T 19587-2017 "Measurement of the specific surface area of solid substances by gas adsorption BET method".
[0058] In some embodiments, the volume average particle size D of the negative electrode hard carbon material of the present invention is v50 is in the range of 1.0-20.0 μm, for example 1.5-15.0 μm. a When the content of D and P in the negative electrode hard carbon material is within the range defined in the present invention, v When the particle size is within the above range, further improved capacity performance and cycle performance can be obtained. v The particle size of 50 refers to the number of particles smaller than the particle size value and particles larger than the particle size value that each account for 50% of the total volume of the negative electrode hard carbon material in the cumulative volume distribution curve of the particle size distribution of the negative electrode hard carbon material. v The particle size is 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 15.5, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, 19.0, 19.5, 20.0 μm, or within the range defined by any two of them. v The 50 particle size can be measured by a measurement method conventionally used in the art, for example, it can be measured by laser diffraction using a Malvern 3000 laser particle size analyzer.
[0059] Preparation method of negative electrode hard carbon material
[0060] The second aspect of the present invention provides a method for preparing the negative electrode hard carbon material according to the first aspect of the present invention, which comprises the following steps:
[0061] (1) treating a carbon source in an air atmosphere at a temperature of 60-300° C., for example, 80-280° C., for 1-24 hours, for example, 2-20 hours;
[0062] (2) adding a phosphorus source to the product obtained in step (1), and then treating the resulting mixture under an inert gas atmosphere at a temperature of 60-300° C., for example, 60-260° C., for 1-12 hours, for example, 2-10 hours;
[0063] (3) pre-carbonizing the product obtained in step (2) at a temperature of 400-650° C., for example, 400-600° C., for 0.5-12 hours, for example, 1-8 hours, under an inert gas atmosphere;
[0064] (4) repeatedly washing the product obtained in step (3) with deionized water until the pH of the product is in the range of 2.0-5.0, and optionally drying;
[0065] (5) uniformly mixing the product obtained in step (4) with at least one of sodium hydroxide, potassium hydroxide, sodium carbonate or potassium carbonate, sodium bicarbonate or potassium bicarbonate powder, and then sintering at a temperature of 500-900° C., such as 550-850° C., under an inert gas atmosphere for 0.5-12 hours, such as 2-10 hours; or
[0066] The product obtained in step (4) is stirred and soaked in at least one of sodium hydroxide, potassium hydroxide, sodium carbonate or potassium carbonate, sodium bicarbonate or potassium bicarbonate solution at a temperature of 20-100° C. for 1-12 hours, and then filtered to obtain a filter cake;
[0067] (6) repeatedly washing the product obtained in step (5) with deionized water until the pH of the product is in the range of 10.0-12.0;
[0068] (7) soaking the product obtained in step (6) in an acid solution at a temperature of 20-100° C. for 1-12 h with stirring, then filtering, and repeatedly washing the filter cake with deionized water until the pH thereof is in the range of 2.0-5.0, and then drying;
[0069] (8) crushing the product obtained in step (7) to D v 50 particle size in the range of 1.0-20.0 μm; and
[0070] (9) The product obtained in step (8) is subjected to high temperature carbonization at a temperature of 1050-1600° C., for example, 1200-1500° C., for 2-8 hours, for example, 2-6 hours, under an inert gas atmosphere, and is optionally crushed.
[0071] Each step of the preparation method of the present invention is described in detail below.
[0072] Step (1)
[0073] In step (1), the carbon source is treated at a temperature of 60-300° C., for example, 80-280° C., for 1-24 hours, for example, 2-20 hours, under air atmosphere (pretreatment).
[0074] The preparation method of the present invention has no particular requirements on the type of carbon source used, but preferably, in some embodiments, the carbon source is selected from one or more of coal, asphalt, and biomass;
[0075] Preferably, the coal is selected from one or more of bituminous coal and lignite;
[0076] Preferably, the asphalt is selected from one or more of medium-temperature asphalt (softening point is 70-115°C, measured according to GB2294-80) and high-temperature asphalt (softening point is 120-280°C, measured according to GB / T 4507-2014);
[0077] Preferably, the biomass is selected from one or more of coconut shell, walnut shell, apricot shell, palm shell, lignin, cellulose, starch, bamboo. As an example, the starch may be corn starch. In some embodiments, the particle size of the corn starch (the particle size corresponding to the mesh number of the sieve used during screening) is 5-20 μm.
[0078] It should be noted that, as Damien has discovered, hard carbon materials made from different types of carbon sources (precursors) may have different degrees of disorder, which will affect fa.
[0079] The purpose of step (1) is to pretreat the carbon source to facilitate subsequent treatment. The treatment process of step (1) can be appropriately adjusted according to the carbon source used, but preferably, the treatment temperature of step (1) is 60-300°C, such as 80-280°C, and the treatment time is 1-24 hours, such as 2-20 hours. As an example, the treatment temperature of step (1) can be 60, 65, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145, 150, 155, 160, 165, 170, 175, 180, 185, 190, 195, 200, 205, 210, 215, 220, 225, 230, 235, 240, 18, 19, 20, 21, 22, 23, 24 hours, or within the range defined by any two of them.
[0080] The above examples illustrate the carbon source type and pretreatment temperature of step (1). It is easy for a person skilled in the art to understand that within the above range of the carbon source type and pretreatment temperature, the person skilled in the art can flexibly adjust the combination of the carbon source type and the pretreatment temperature to achieve a better pretreatment effect.
[0081] Step (2)
[0082] After pretreating the carbon source, a phosphorus source is added to the product obtained in step (1), and the resulting mixture is then treated at 60-300° C., such as 60-260° C., for 1-12 hours, such as 2-10 hours, under an inert gas atmosphere.
[0083] The preparation method of the present invention has no particular requirements on the type of phosphorus source used, but preferably, in some embodiments, the phosphorus source is selected from one or more of phosphoric acid or phosphates, preferably selected from one or more of phosphoric acid, ammonium dihydrogen phosphate, sodium dihydrogen phosphate, potassium dihydrogen phosphate, and more preferably selected from one or more of phosphoric acid and ammonium dihydrogen phosphate. When the phosphorus source is selected from the above types, especially phosphoric acid or diammonium hydrogen phosphate, it is beneficial to further improve the comprehensive properties of the hard carbon material, especially the capacity performance.
[0084] The preparation method of the present invention has no special requirements for the specific amount of the phosphorus source, as long as the final doping amount of the phosphorus element is within the range defined by the present invention, but preferably, in some embodiments, the weight ratio of the product obtained in step (1) to the phosphorus element in the phosphorus source is 100:5 to 100:45, for example, 100:5 to 100:30. For example, the weight ratio of the product obtained in step (1) to the phosphorus element in the phosphorus source is 100:5, 100:6, 100:8, 100:10, 100:15, 100:20, 100:25, 100:30, 100:35, 100:40, or within the range defined by any two of them. In some embodiments, when the phosphorus source is selected from one or more of phosphoric acid, ammonium dihydrogen phosphate, sodium dihydrogen phosphate, and potassium dihydrogen phosphate, the weight ratio of the product obtained in step (1) to the phosphorus source is 100:5 to 100:100, for example, 100:30 to 100:100. As an example, the weight ratio of the product obtained in step (1) to the phosphorus source is 100:5, 100:10, 100:15, 100:20, 100:25, 100:30, 100:35, 100:40, 100:45, 100:50, 100:55, 100:60, 100:65, 100:70, 100:75, 100:80, 100:85, 100:90, 100:95, 100:100, or within the range defined by any two of them. By controlling the amount of phosphorus source added, the P content of the hard carbon material can be adjusted and the disorder parameter f can be affected. a .
[0085] After the product obtained in step (1) is uniformly mixed with a phosphorus source, the mixture is treated under an inert gas atmosphere at a temperature of 60-300° C., for example, 60-260° C., for 1-12 hours, for example, 2-10 hours. As an example, the treatment temperature may be 60, 65, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145, 150, 155, 160, 165, 170, 175, 180, 185, 190, 195, 200, 205, 210, 215, 220, 230, 240, 250, 260, 270, 280, 290, 300, 310, 320, 330, 340, 350, 360, 370, 380, 390, 400, 410, 420, 430, 440, 450, 460, 470, 480, 490, 500, 510, 520, 530, 540, 550 The temperature of the inert gas may be 25, 230, 235, 240, 245, 250, 255, 260, 265, 270, 275, 280, 285, 290, 295, 300° C., or any two thereof, and / or the treatment time may be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 hours, or any two thereof. As an example, the inert gas may be an inert gas commonly used by those skilled in the art, such as nitrogen, helium, argon, etc.
[0086] Step (3)
[0087] The product obtained in step (2) is pre-carbonized under an inert gas atmosphere at a temperature of 400-650° C., for example, 400-600° C., for 0.5-12 hours, for example, 1-8 hours.
[0088] The pre-carbonization temperature also affects the P content and disorder parameter f of the final hard carbon material. a It should be noted that the pre-carbonization temperature should not be too high to avoid the P in the material from forming high polyphosphate, which becomes difficult to remove and leads to excessively high P content in the final product. In some embodiments, the pre-carbonization temperature may be 400, 410, 420, 430, 440, 450, 460, 470, 480, 490, 500, 510, 520, 530, 540, 550, 560, 570, 580, 590, 600, 610, 620, 630, 640, 650° C., or in the range defined by any two of them, and / or the pre-carbonization time may be 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12 hours, or in the range defined by any two of them. The inert gas may be an inert gas commonly used by those skilled in the art, such as nitrogen, helium, argon, etc.
[0089] Step (4)
[0090] After the mixture of the carbon source and the phosphorus source is pre-carbonized, the product obtained in step (3) is repeatedly washed with deionized water in step (4) until the pH of the product is in the range of 2.0-5.0, and optionally dried.
[0091] By repeatedly washing with deionized water, some impurities in the product obtained in step (3) can be removed. Preferably, in some embodiments, in step (4), the product obtained in step (3) is washed with deionized water until the pH of the product is in the range of 2.0-5.0, for example, washed to a pH of 2.0, 2.2, 2.4, 2.6, 2.8, 3.0, 3.2, 3.4, 3.6, 3.8, 4.0, 4.2, 4.4, 4.6, 4.8, 5.0, or within the range defined by any two of them.
[0092] In some embodiments, preferably, after washing with deionized water, the obtained product is dried to facilitate subsequent processes. The preparation method of the present invention has no special requirements for the drying process, and the drying can be carried out using a drying method commonly used by those skilled in the art.
[0093] Step (5)
[0094] In step (5), the product obtained in step (4) is treated with sodium hydroxide, potassium hydroxide, sodium carbonate or potassium carbonate, sodium bicarbonate or potassium bicarbonate powder or their aqueous solution. Alkali treatment plays an important role in reducing the phosphorus content, and can remove phosphorus that cannot be washed off by water in step (4) and phosphorus on the carbon skeleton. If the alkali treatment step is not added, the phosphorus content may exceed the limit value.
[0095] In step (5), the product obtained in step (4) is uniformly mixed with at least one of sodium hydroxide, potassium hydroxide, sodium carbonate or potassium carbonate, sodium bicarbonate or potassium bicarbonate powder, and then sintered at a temperature of 500-900° C., such as 550-850° C., under an inert gas atmosphere for 0.5-12 hours, such as 2-10 hours; or
[0096] The product obtained in step (4) is stirred and soaked in at least one of sodium hydroxide, potassium hydroxide, sodium carbonate or potassium carbonate, sodium bicarbonate or potassium bicarbonate solution at a temperature of 20-100° C. for 1-12 hours, and then filtered to obtain a filter cake.
[0097] In step (5), the product obtained in step (4) can be treated in one of the two ways mentioned above.
[0098] In some embodiments, the product obtained in step (4) is treated by way 1. For example, at least one of sodium hydroxide, potassium hydroxide, sodium carbonate or potassium carbonate, sodium bicarbonate or potassium bicarbonate powder, or a mixture of two or more thereof may be added to the product obtained in step (4), and mixed uniformly, and then sintered at a temperature of 500-900° C., such as 550-850° C., under an inert gas atmosphere for 0.5-12 hours, such as 2-10 hours. As an example, the sintering temperature may be 500, 510, 520, 530, 540, 550, 560, 570, 580, 590, 600, 610, 620, 630, 640, 650, 660, 670, 680, 690, 700, 710, 720, 730, 740, 750, 760, 770, 780, 790, 800, 810, 820, 830, 840 0, 850, 860, 870, 880, 890, 900 ° C, or any two of them within the range defined, and / or the sintering time can be 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12 hours, or any two of them within the range defined. The inert gas can be an inert gas commonly used by those skilled in the art, such as nitrogen, helium, argon, etc.
[0099] The preparation method of the present invention has no particular requirement on the amount of added sodium hydroxide, potassium hydroxide, sodium carbonate or potassium carbonate, sodium bicarbonate or potassium bicarbonate powder, as long as it is sufficient to adjust the product obtained in step (4) to alkalinity, for example, pH greater than 10.0.
[0100] In some embodiments, based on 100% by weight of the product obtained in step (4), the amount of sodium hydroxide, potassium hydroxide, sodium carbonate or potassium carbonate, sodium bicarbonate or potassium bicarbonate powder added by dry weight is in the range of 5-50% by weight. As an example, the amount of sodium hydroxide, potassium hydroxide, sodium carbonate or potassium carbonate, sodium bicarbonate or potassium bicarbonate powder added by dry weight may be 5, 10, 15, 20, 25, 30, 35, 40, 45, 50% by weight, or within the range defined by any two of them.
[0101] In some embodiments, the product obtained in step (4) is treated by mode 2. For example, the product obtained in step (4) can be stirred and soaked for 1-12 hours with at least one of sodium hydroxide, potassium hydroxide, sodium carbonate or potassium carbonate, sodium bicarbonate or potassium bicarbonate solution at a temperature of 20-100° C., and then filtered to obtain a filter cake. As an example, the temperature for stirring and soaking treatment can be 20, 25, 30, 35, 40, 45, 50, 60, 65, 70, 75, 80, 85, 90, 95, 100° C., or within the range defined by any two of them, and / or the time for stirring and soaking treatment can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 hours, or within the range defined by any two of them.
[0102] Similarly, the preparation method of the present invention has no particular requirements on the amount of sodium hydroxide, potassium hydroxide, sodium carbonate or potassium carbonate, sodium bicarbonate or potassium bicarbonate solution, as long as it is sufficient to adjust the product obtained in step (4) to alkalinity, for example, pH greater than 10.0.
[0103] In some embodiments, the concentration of sodium hydroxide, potassium hydroxide, sodium carbonate or potassium carbonate, sodium bicarbonate or potassium bicarbonate solution is 0.5-40% by weight. As an example, the concentration of sodium hydroxide, potassium hydroxide, sodium carbonate or potassium carbonate, sodium bicarbonate or potassium bicarbonate solution can be 0.5, 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 11.0, 12.0, 13.0, 14.0, 15.0, 16.0, 17.0, 18.0, 19.0, 20.0, 25.0, 30.0, 35.0, 40.0% by weight, or any two of them.
[0104] Step (6)
[0105] In step (6), the product obtained in step (5) is repeatedly washed with deionized water until the pH of the product is in the range of 10.0-12.0.
[0106] Preferably, in some embodiments, in step (6), the product obtained in step (5) is washed with deionized water until the pH of the product is in the range of 10.0-12.0, for example, washed to a pH of 10.0, 10.5, 11.0, 11.5, 12.0, or within the range defined by any two of them.
[0107] Step (7)
[0108] In step (7), the product obtained in step (6) is stirred and soaked in an acid solution at a temperature of 20-100° C. for 1-12 hours, then filtered, and the filter cake is repeatedly washed with deionized water until its pH is in the range of 2.0-5.0, and then dried.
[0109] The product obtained in step (6) can be made acidic again by treating with an acid solution. The preparation method of the present invention has no particular requirements for the acid solution used, but preferably, the concentration of the acid solution is 0.5-30% by weight, such as 0.5-20% by weight or 1.0-15% by weight; and / or the acid solution is selected from one or more of hydrochloric acid, sulfuric acid, nitric acid, hydrofluoric acid, citric acid, and acetic acid, preferably one or more of hydrochloric acid, sulfuric acid, and nitric acid. As an example, the concentration of the acid solution can be 0.5, 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 11.0, 12.0, 13.0, 14.0, 15.0, 16.0, 17.0, 18.0, 19.0, 20.0, 25.0, 30.0% by weight, or within the range defined by any two of them.
[0110] As mentioned above, in step (7), the product obtained in step (6) is stirred and soaked in an acid solution at a temperature of 20-100° C. for 1-12 hours, and then filtered. As an example, the temperature for stirring and soaking treatment can be 20, 25, 30, 35, 40, 45, 50, 60, 65, 70, 75, 80, 85, 90, 95, 100° C., or within the range defined by any two of them, and / or the time for stirring and soaking treatment can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 hours, or within the range defined by any two of them.
[0111] In some embodiments, in step (7), the filtered product after the acid solution stirring and soaking treatment is washed repeatedly with deionized water until the pH of the product is in the range of 2.0-5.0, for example, washed to a pH of 2.0, 2.2, 2.4, 2.6, 2.8, 3.0, 3.2, 3.4, 3.6, 3.8, 4.0, 4.2, 4.4, 4.6, 4.8, 5.0, or within the range defined by any two of them.
[0112] In some embodiments, preferably, after washing with deionized water, the obtained product is dried to facilitate subsequent processes. The preparation method of the present invention has no special requirements for the drying process, and the drying can be carried out using a drying method commonly used by those skilled in the art.
[0113] Step (8)
[0114] In step (8), the product obtained in step (7) is crushed to Dv 50 The particle size is in the range of 1.0-20.0 μm.
[0115] The preparation method of the present invention has no particular limitation on the crushing method, and the crushing can be carried out by the methods commonly used in the art, such as air flow mill, mechanical mill, sand mill, ball mill, etc. As an example, the product obtained in step (7) can be crushed to D v The particle size is 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 11.0, 12.0, 13.0, 14.0, 15.0, 16.0, 17.0, 18.0, 19.0, 20.0 μm, or within the range defined by any two of them.
[0116] Step (9)
[0117] In step (9), the product obtained in step (8) is subjected to high temperature carbonization at 1050-1600° C., for example, 1200-1500° C., for 2-8 hours, for example, 2-6 hours, under an inert gas atmosphere, and is optionally crushed.
[0118] As an example, the temperature of high temperature carbonization may be 1050, 1060, 1080, 1090, 1100, 1110, 1120, 1130, 1150, 1160, 1180, 1200, 1220, 1240, 1250, 1260, 1290, 1300, 1320, 1340, 1350, 1370, 1390, 1400, 1420, 1440, 1450, 1470, 1490, 1500, 1520, 1540, 1550, 1570, 1590, 1600°C, or within the range defined by any two of them, and / or the time of high temperature carbonization may be 2, 3, 4, 5, 6, 7, 8 hours, or within the range defined by any two of them. As the high temperature carbonization temperature increases, the P content and f a May decline.
[0119] In some embodiments, the high-temperature carbonization product is optionally crushed so that the volume average particle size D of the obtained hard carbon material is v 50 is in the range of 1.0-20.0 μm, for example, 1.5-15.0 μm.
[0120] Negative electrode composition
[0121] A third aspect of the present invention provides a negative electrode composition, which is a negative electrode composition for a sodium ion secondary battery, comprising the negative electrode hard carbon material according to the first aspect of the present invention.
[0122] In addition to the negative electrode hard carbon material of the present invention, the negative electrode composition (for sodium ion secondary battery) may further include a conductive agent, a binder and any other substances that can be used by those skilled in the art as needed, such as a dispersant and an additive for improving stability.
[0123] In some embodiments, based on the dry weight of the negative electrode composition (for sodium ion secondary battery), the content of the negative electrode hard carbon material may be a common amount in the art, for example, 70-95 wt %, for example 80-90 wt %.
[0124] The type of conductive agent is not particularly limited, as long as it has the properties of enhancing the conductivity of the negative electrode and not adversely affecting the performance of the negative electrode hard carbon material. Those skilled in the art can select the conductive agent commonly used in the art according to actual needs. As an example, the conductive agent used for the negative electrode composition (for sodium ion secondary battery) can be selected from one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0125] In some embodiments, based on the dry weight of the negative electrode composition (for sodium ion secondary battery), the content of the conductive agent may be a common amount in the art, such as 1-10 wt %, such as 2-5 wt %.
[0126] The binder is not particularly limited, as long as it has the properties of enhancing the adhesion between the particles of the negative electrode hard carbon material and the adhesion to the current collector and does not adversely affect the performance of the negative electrode hard carbon material. Those skilled in the art can select according to actual needs. As an example, the binder for the negative electrode composition for the sodium ion secondary battery can be selected from polyfluoroolefin binders such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA) or their modified (for example, carboxylic acid, acrylic acid, acrylonitrile, etc.) derivatives and styrene-butadiene rubber, acrylic resin, carboxymethyl cellulose, polyvinyl alcohol (PVA) and the like One or more.
[0127] In some embodiments, based on the dry weight of the negative electrode composition (for a sodium ion secondary battery), the content of the binder is 1-10 wt %, for example, 2-5 wt %.
[0128] The negative electrode composition may be in the form of a slurry, ie, it may further include a solvent. The negative electrode composition may also be in a dry form, ie, it does not include a solvent, for example, it may be in the form of a negative electrode active material layer disposed on a negative electrode current collector.
[0129] Sodium ion secondary battery
[0130] A fourth aspect of the present invention provides a sodium ion secondary battery. A sodium ion secondary battery generally includes a positive electrode, a negative electrode, a separator and an electrolyte.
[0131] In some embodiments, the sodium ion secondary battery may further include an outer package for encapsulating the electrode assembly and the electrolyte. For example, the outer package may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc., or a soft package, such as a bag-type soft package, such as a soft package made of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0132] The shape of the sodium ion secondary battery is not particularly limited, and it may be cylindrical, square, or any other shape.
[0133] The sodium ion secondary battery can be prepared by a method commonly used in the art. For example, the positive electrode sheet, the negative electrode sheet and the separator can be made into a battery cell through a winding process or a lamination process, and then the electrolyte is injected.
[0134] positive electrode
[0135] The positive electrode (or positive electrode sheet) includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector.
[0136] The positive electrode current collector is not particularly limited, and the positive electrode current collector commonly used by those skilled in the art can be used. As an example, the positive electrode current collector can be a metal foil such as aluminum foil, nickel foil, or a composite current collector. The composite current collector can be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), 1,3-propane sultone (PS), polyethylene (PE), etc.), but the present invention is not limited to these materials.
[0137] The present invention has no particular limitation on the positive electrode active material, and the positive electrode active material commonly used in the art can be used. For example, the positive electrode active material can be selected from one or more of a layered transition metal oxide or a Prussian blue analog. As an example, the layered transition metal oxide can have a general formula of Na x M y O 2 , wherein M is selected from one or more of Mn, Fe, Ni, Co, Cr, Ti, Zn, V, Al, Zr, Ce and Mg, and the general formula satisfies the valence balance. In addition, the layered transition metal oxide may be doped with an element with high electronegativity, such as one or more of S, N, F, Br, Cl, I, CN, etc. As an example, the positive electrode active material may be selected from NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 、Na 2FeP 2 O 7 、Na 4 Fe 3 (PO 4 ) 2 (P 2 O 7 ), Na 3 V 2 (PO 4 ) 3 、NaFePO 4 and NaMnFe(CN) 6 One or more of the above.
[0138] In some embodiments, based on the total weight (dry weight) of the positive electrode active material layer, the content of the positive electrode material may be a common amount in the art, for example, 70-95 wt %, for example 80-90 wt %.
[0139] In addition to the positive electrode active material, the positive electrode active material layer may further include a binder, a conductive agent and any other optional auxiliary agents such as a thickener.
[0140] There is no particular requirement for the positive electrode conductive agent. As an example, the conductive agent can be selected from one or more of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0141] In some embodiments, the conductive agent may be present in an amount of 1-10 wt %, for example 2-5 wt %, based on the total weight (dry weight) of the positive electrode active material layer.
[0142] There is no special requirement for the positive electrode binder. As an example, the binder is selected from one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), styrene butadiene rubber (SBR), water-based acrylic resin and carboxymethyl cellulose (CMC).
[0143] In some embodiments, the content of the binder may be 1-10 wt %, for example 2-5 wt %, based on the total weight (dry weight) of the positive electrode active material layer.
[0144] The positive electrode sheet can be prepared according to the method commonly used in the art.
[0145] For example, the positive electrode can be formed by uniformly dispersing a positive electrode active material, a conductive agent, and a binder in a solvent (eg, N-methylpyrrolidone (NMP)) to obtain a positive electrode slurry; coating the slurry on a positive electrode current collector, drying, and pressing.
[0146] Alternatively, the positive electrode can also be formed by uniformly dispersing the positive electrode active material, the conductive agent, and the binder in a solvent (e.g., N-methylpyrrolidone (NMP)) to obtain a positive electrode slurry; casting the positive electrode slurry on a separate carrier, drying, separating the obtained positive electrode film from the carrier and laminating it on a positive electrode current collector.
[0147] negative electrode
[0148] The negative electrode comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, the negative electrode active material layer comprising the negative electrode composition of the third aspect of the present invention, for example in dry form. The negative electrode also forms an aspect of the present invention.
[0149] The negative electrode current collector is not particularly limited, and the negative electrode current collector commonly used by those skilled in the art can be used. As an example, the negative electrode current collector can be a metal foil such as copper foil, aluminum foil or a composite current collector. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector can be formed by forming a metal material (copper, aluminum, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.), but the present invention is not limited to these materials.
[0150] The negative electrode can be prepared according to a method commonly used in the art.
[0151] For example, the negative electrode can be formed by uniformly dispersing the negative electrode active material and optional conductive agent, binder and thickener in a solvent (such as N-methylpyrrolidone (NMP) or deionized water) to form a negative electrode slurry; coating the negative electrode slurry on a negative electrode current collector, drying, and pressing.
[0152] Alternatively, the negative electrode can also be formed by uniformly dispersing the negative electrode active material and optional conductive agent, binder and thickener in a solvent (e.g., N-methylpyrrolidone (NMP) or deionized water) to form a negative electrode slurry; casting the negative electrode slurry on a separate carrier, drying, separating the obtained negative electrode film from the carrier and laminating it on a negative electrode current collector.
[0153] Electrolytes
[0154] The electrolyte plays a role of conducting ions between the positive electrode plate and the negative electrode plate. The electrolyte is not particularly limited and can be selected as needed. For example, the electrolyte can be selected from at least one of a solid electrolyte, a gel electrolyte, and a liquid electrolyte (i.e., an electrolyte).
[0155] In some embodiments, the electrolyte is an electrolyte solution, which includes an organic aprotic solvent and an electrolyte sodium salt.
[0156] In some embodiments, the solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0157] In some embodiments, the electrolyte sodium salt may be selected from sodium hexafluorophosphate (NaPF 6 ), sodium tetrafluoroborate (NaBF 4 ), sodium perchlorate (NaClO 4 ), sodium hexafluoroborate (NaBF 6 ), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethylsulfonyl)imide (NaTFSI), sodium trifluoromethylsulfonate (NaTFS), sodium difluorooxalatoborate (NaDFOB), sodium dioxalatoborate (NaBOB), sodium difluorophosphate (NaPO 2 F 2 ), sodium difluorobis(oxalate) phosphate (NaDFOP) and sodium tetrafluorobis(oxalate) phosphate (NaTFOP).
[0158] In some embodiments, the concentration of sodium ions in the electrolyte is 0.2-2 mol / L, such as 0.5-1.0 mol / L.
[0159] In some embodiments, the electrolyte may further include additives, for example, additives that help negative electrode film formation or positive electrode film formation, and additives that can improve battery performance, such as additives that improve high or low temperature performance of the battery.
[0160] Diaphragm
[0161] The separator is not particularly limited, and a commonly used porous structure separator with electrochemical stability and chemical stability can be used, for example, it can be a single layer or multilayer film of one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. When a solid electrolyte is used, the separator can also be omitted.
[0162] use
[0163] The fifth aspect of the present invention provides the use of the sodium ion secondary battery according to the fourth aspect of the present invention in an energy storage device for solar power generation, wind power generation, smart grid peak regulation, distributed power stations, backup power supplies or communication base stations.
[0164] Those skilled in the art will appreciate that the sodium ion secondary battery of the fourth aspect of the present invention may also be used for other purposes. For example, the sodium ion secondary battery may be used as a power source or energy storage unit in a mobile device (e.g., a mobile phone, etc.), an electric vehicle (e.g., a pure electric vehicle, a hybrid electric vehicle, an electric bicycle, an electric scooter, etc.), an electric train, etc.
[0165] Example
[0166] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0167] 1. Preparation Example
[0168] Example 1
[0169] A high-temperature asphalt (particle size 500 mesh, mesh number, the same below) with a softening point of 250°C was selected as the carbon source, and 100g of asphalt was treated at 220°C for 20h in an air atmosphere. The treated asphalt was then evenly mixed with 60g of phosphoric acid solution (50wt%) and treated at 250°C for 4h in a nitrogen atmosphere. The resulting product was then pre-carbonized at 500°C for 2h in a nitrogen atmosphere. After cooling to room temperature, the pre-carbonized product was repeatedly washed with deionized water until the pH of the product (i.e., the pH of the washing solution, the same below) was 2.5±0.5, and dried at 120°C. After cooling to room temperature, 400ml of sodium hydroxide solution (20wt%) was added to the dried product, and stirred and soaked at 80°C for 4h, and filtered. Subsequently, the filtered product (filter cake, the same below) was repeatedly washed with deionized water until the pH of the product was 11±0.5. 400 ml of hydrochloric acid solution (15 wt%) was added to the obtained product, and stirred and soaked at 80 ° C for 4 h, and filtered. The filtered product (filter cake, the same below) was then repeatedly washed with deionized water until the pH of the product was 2.5 ± 0.5, and then dried at 120 ° C. The dried product was ball milled using a ball mill (model: SFM-3 high-speed three-dimensional pendulum ball mill, manufacturer: Shenzhen Kejing Zhida Technology Co., Ltd., the same below) until the product D vThe ball milled product was then carbonized at 1500°C for 3 h in an argon atmosphere and then naturally cooled to room temperature to obtain the final product, hard carbon. v 50The particle size is 9.3μm.
[0170] Example 2
[0171] High temperature asphalt (500 mesh) with a softening point of 250°C was selected as the carbon source. The experimental steps were the same as those in Example 1, but the amount of phosphoric acid (50 wt%) was 100 g. The D v 50The particle size is 9.7μm.
[0172] Example 3
[0173] High temperature asphalt (500 mesh) with a softening point of 250°C was selected as the carbon source. The experimental steps were the same as those in Example 1, but the amount of phosphoric acid (50 wt%) was 140 g. The D v 50The particle size is 9.8μm.
[0174] Example 4
[0175] High temperature asphalt (500 mesh) with a softening point of 250°C was selected as the carbon source. The experimental steps were the same as those in Example 1, but the amount of phosphoric acid (50 wt%) was 180 g. The D v 50The particle size is 9.5μm.
[0176] Comparative Example 1
[0177] High-temperature asphalt (particle size 500 mesh) with a softening point of 250°C was selected as the carbon source, and 100g of asphalt was treated at 280°C for 12h in an air atmosphere. The treated asphalt was then pre-carbonized at 500°C for 2h in a nitrogen atmosphere. After cooling to room temperature, 400ml of sodium hydroxide solution (20wt%) was added to the pre-carbonized product, and stirred and soaked at 80°C for 4h, and filtered. Subsequently, deionized water was used for repeated washing until the pH of the product was 11±0.5. 400ml of hydrochloric acid solution (15wt%) was added to the resulting product, and stirred and soaked at 80°C for 4h, and filtered, and then deionized water was used for repeated washing until the pH of the product was 2.5±0.5, and then dried at 120°C. The dried product was ball milled using a ball mill to product D v The ball milled product was then carbonized at 1500°C for 3 h in an argon atmosphere and then naturally cooled to room temperature to obtain the final product, hard carbon. v 50The particle size is 9.8μm.
[0178] Comparative Example 2
[0179] High temperature asphalt (500 mesh) with a softening point of 250°C was selected as the carbon source. The experimental steps were the same as those in Example 1, but the amount of phosphoric acid (50 wt%) was 220 g. The D v 50The particle size is 9.7μm.
[0180] Example 5
[0181] Coconut shell (particle size 80 mesh) was selected as the carbon source, and 100g of coconut shell was treated at 120°C for 12h in an air atmosphere. The treated coconut shell was then evenly mixed with 60g of phosphoric acid (50wt%) and treated at 150°C for 4h in a nitrogen atmosphere. The resulting product was then pre-carbonized at 400°C for 2h in a nitrogen atmosphere. After cooling to room temperature, the pre-carbonized product was repeatedly washed with deionized water until the pH was 2.5±0.5 and dried at 120°C. After cooling to room temperature, 400ml of potassium hydroxide solution (20wt%) was added to the dried product, and stirred and soaked at 80°C for 4h, and filtered. The filtered product was then repeatedly washed with deionized water until the pH of the product was 11±0.5. 400 ml of nitric acid solution (10 wt%) was added to the obtained product, and stirred and soaked at 80 ° C for 4 h, and filtered. The filtered product was then repeatedly washed with deionized water until the pH of the product was 2.5 ± 0.5, and then dried at 120 ° C. The dried product was ball milled using a ball mill until the product D v 50 particle size is 6.0μm. Then the ball-milled product is carbonized at 1400℃ for 3h in an argon atmosphere and cooled naturally to room temperature to obtain the final product hard carbon. v 50The particle size is 5.5μm.
[0182] Example 6
[0183] Coconut shell (size 80 mesh) was selected as the carbon source. The experimental steps were the same as those in Example 5, but the pre-carbonization temperature was 500°C. The D v 50The particle size is 5.2μm.
[0184] Example 7
[0185] Coconut shell (size 80 mesh) was selected as the carbon source. The experimental steps were the same as those in Example 5, but the pre-carbonization temperature was 600°C. The D v 50The particle size is 5.3μm.
[0186] Comparative Example 3
[0187] Coconut shell (size 80 mesh) was selected as the carbon source. The experimental steps were the same as those in Example 5, but the pre-carbonization temperature was 700°C. The D v 50The particle size is 5.2μm.
[0188] Comparative Example 4
[0189] Coconut shell (particle size 80 mesh) was selected as the carbon source, and 100g of coconut shell was treated at 150°C for 12h in an air atmosphere. The treated coconut shell was then evenly mixed with 60g of phosphoric acid (50wt%) and treated at 200°C for 2h in a nitrogen atmosphere. The resulting product was pre-carbonized at 500°C for 2h in a nitrogen atmosphere. After cooling to room temperature, the pre-carbonized product was repeatedly washed with deionized water until the pH was 2.5±0.5, and dried at 120°C. After cooling to room temperature, 400ml of hydrochloric acid solution (15wt%) was added to the resulting product, and it was stirred and soaked at 80°C for 4h, and filtered. Subsequently, the filtered product was repeatedly washed with deionized water until the pH of the product was 2.5±0.5, and then dried at 120°C. The dried product was ball milled using a ball mill until product D v 50 particle size is 6.0μm. Then the ball-milled product is carbonized at 1400℃ for 3h in an argon atmosphere and cooled naturally to room temperature to obtain the final product hard carbon. v 50The particle size is 5.4μm.
[0190] Comparative Example 5
[0191] Coconut shell (particle size 80 mesh) was selected as the carbon source. The experimental steps were the same as those in Comparative Example 1, except that the high-temperature carbonization temperature was 1400°C, and the sodium hydroxide solution (20wt%) was replaced by potassium hydroxide solution (20wt%). The D v 50The particle size is 5.3μm.
[0192] Comparative Example 6
[0193] Coconut shell (size 80 mesh) was selected as the carbon source. The experimental steps were the same as those in Example 5, but the pre-carbonization temperature was 500°C and the high-temperature carbonization temperature was 1000°C. The D v 50The particle size is 5.5μm.
[0194] Example 8
[0195] Coconut shell (size 80 mesh) was selected as the carbon source. The experimental steps were the same as those in Example 5, but the pre-carbonization temperature was 500°C and the high-temperature carbonization temperature was 1200°C. The D v 50The particle size is 5.2μm.
[0196] Example 9
[0197] Coconut shell (size 80 mesh) was selected as the carbon source. The experimental steps were the same as those in Example 5, but the pre-carbonization temperature was 500°C and the high-temperature carbonization temperature was 1500°C. The D v 50The particle size is 5.3μm.
[0198] Example 10
[0199] Bituminous coal (particle size 500 mesh) was selected as the carbon source, and 100g of bituminous coal was treated at 220°C for 12h in an air atmosphere. The treated bituminous coal was then evenly mixed with 100g of phosphoric acid (50wt%) and treated at 250°C for 4h in a nitrogen atmosphere. The resulting product was pre-carbonized at 500°C for 2h in a nitrogen atmosphere. After cooling to room temperature, the pre-carbonized product was repeatedly washed with deionized water until the pH was 2.5±0.5, and dried at 120°C. After cooling to room temperature, 400ml of sodium hydroxide solution (20wt%) was added to the dried product, and stirred and soaked at 80°C for 4h, and filtered. The filtered product was then repeatedly washed with deionized water until the pH of the product was 11±0.5. 400 ml of nitric acid solution (10 wt%) was added to the obtained product, and stirred and soaked at 80 ° C for 4 h, and filtered. The filtered product was then repeatedly washed with deionized water until the pH of the product was 2.5 ± 0.5, and then dried at 120 ° C. The dried product was ball milled using a ball mill until the product D v 50 particle size is 8.0μm. Then the ball-milled product is carbonized at 1400℃ for 3h in an argon atmosphere and cooled naturally to room temperature to obtain the final product, hard carbon. v 50The particle size is 7.2μm.
[0200] Embodiment 11
[0201] Lignite with a particle size of 500 mesh was selected as the carbon source, and 100g of lignite was treated at 150°C for 8h in an air atmosphere. The treated lignite was then evenly mixed with 100g of phosphoric acid (50wt%) and treated at 200°C for 4h in a nitrogen atmosphere. The resulting product was then pre-carbonized at 500°C for 2h in a nitrogen atmosphere. After cooling to room temperature, the pre-carbonized product was repeatedly washed with deionized water until the pH of the product was 11±0.5, and dried at 120°C. After cooling to room temperature, 400ml of sodium hydroxide solution (20wt%) was added to the dried product, and stirred and soaked at 80°C for 4h, and filtered. The resulting product was then repeatedly washed with deionized water until the pH of the product was 11±0.5. 400 ml of sulfuric acid solution (10 wt%) was added to the obtained product, and stirred and soaked at 80 ° C for 4 h, and filtered, and then repeatedly washed with deionized water until the pH of the product was 2.5 ± 0.5, and dried at 120 ° C. The dried product was ball milled using a ball mill until the product D v 50 particle size is 8.0μm. Then the ball-milled product is carbonized at 1400℃ for 3h in an argon atmosphere and cooled naturally to room temperature to obtain the final product, hard carbon. v 50The particle size is 7.1μm.
[0202] Example 12
[0203] Corn starch (15.2 μm) was selected as the carbon source, and 100 g of starch was treated at 220 ° C for 12 h in an air atmosphere. The treated starch was then evenly mixed with 60 g of phosphoric acid (50 wt%) and treated at 150 ° C for 4 h in a nitrogen atmosphere. The resulting product was pre-carbonized at 500 ° C for 2 h in a nitrogen atmosphere. After cooling to room temperature, the pre-carbonized product was repeatedly washed with deionized water until the pH of the product was 2.5 ± 0.5, and dried at 120 ° C. After cooling to room temperature, 400 ml of sodium hydroxide solution (20 wt%) was added to the dried product, and stirred and soaked at 80 ° C for 4 h, and filtered. The resulting product was then repeatedly washed with deionized water until the pH of the product was 11 ± 0.5. 400 ml of hydrochloric acid solution (8 wt%) was added to the obtained product, and stirred and soaked at 80 ° C for 4 h, and filtered, and then repeatedly washed with deionized water until the pH of the product was 2.5 ± 0.5, and dried at 120 ° C. The dried product was ball milled using a ball mill until the product D v 50 particle size is 8.0μm. Then the ball-milled product is carbonized at 1400℃ for 3h in an argon atmosphere and cooled naturally to room temperature to obtain the final product, hard carbon. v 50The particle size is 7.4μm.
[0204] Embodiment 13
[0205] Dry bamboo (80 mesh bamboo powder) was selected as the carbon source, and the experimental steps were the same as in Example 12. The D v 50The particle size is 7.1μm.
[0206] Embodiment 14
[0207] Coconut shell (particle size 80 mesh) was selected as the carbon source. The experimental steps were the same as those in Example 6, except that phosphoric acid (50 wt%) was replaced by ammonium dihydrogen phosphate solution (50 wt%), and potassium hydroxide solution (20 wt%) was replaced by sodium hydroxide solution (20 wt%). The D of the obtained hard carbon was v 50The particle size is 5.3μm.
[0208] Embodiment 15
[0209] Coconut shell (particle size 80 mesh) was selected as the carbon source. The experimental steps were the same as those in Example 6, except that phosphoric acid (50 wt%) was replaced by sodium dihydrogen phosphate solution (50 wt%), and potassium hydroxide solution (20 wt%) was replaced by sodium hydroxide solution (20 wt%). The D of the obtained hard carbon was v 50The particle size is 5.1μm.
[0210] Example 16
[0211] Coconut shell (particle size 80 mesh) was selected as the carbon source. The experimental steps were the same as those in Example 6, except that phosphoric acid (50 wt%) was replaced by potassium dihydrogen phosphate solution (50 wt%), and potassium hydroxide solution (20 wt%) was replaced by sodium hydroxide solution (20 wt%). The D of the obtained hard carbon was v 50The particle size is 5.3μm.
[0212] Embodiment 17
[0213] Coconut shell (particle size 80 mesh) was selected as the carbon source, and 100g of coconut shell was treated at 120°C for 12h in an air atmosphere. The treated coconut shell was then evenly mixed with 60g of phosphoric acid (50wt%) and treated at 150°C for 4h in a nitrogen atmosphere. The resulting product was then pre-carbonized at 500°C for 2h in a nitrogen atmosphere. After cooling to room temperature, the pre-carbonized product was repeatedly washed with deionized water until the pH was 2.5±0.5 and dried at 120°C. 20wt% sodium hydroxide powder (based on the weight of the dried product, the same below) was added to the dried product, mixed evenly, and sintered at 550°C for 2 hours in an inert gas atmosphere. The product was then repeatedly washed with deionized water until the pH of the product was 11±0.5. 400 ml of nitric acid solution (10 wt%) was added to the obtained product, and stirred and soaked at 80 ° C for 4 h, and filtered. The filtered product was then repeatedly washed with deionized water until the pH of the product was 2.5 ± 0.5, and then dried at 120 ° C. The dried product was ball milled using a ball mill until the product D v 50 particle size is 6.0μm. Then the ball-milled product is carbonized at 1400℃ for 3h in an argon atmosphere and cooled naturally to room temperature to obtain the final product hard carbon. v 50The particle size is 5.2μm.
[0214] Embodiment 18
[0215] Coconut shell (size 80 mesh) was selected as the carbon source, and the experimental steps were the same as in Example 17, except that the sodium hydroxide powder was replaced by potassium hydroxide powder. v 50The particle size is 5.0μm.
[0216] Comparative Example 7
[0217] Coconut shell (80 mesh) was selected as the carbon source, and the experimental steps were the same as in Example 17, except that the sodium hydroxide powder was replaced by calcium carbonate powder. v 50The particle size is 5.1μm.
[0218] Embodiment 19
[0219] Coconut shell (particle size 80 mesh) was selected as the carbon source, and 100g of coconut shell was treated at 120°C for 12h in an air atmosphere. The treated coconut shell was then evenly mixed with 60g of phosphoric acid (50wt%) and treated at 150°C for 4h in a nitrogen atmosphere. The resulting product was then pre-carbonized at 500°C for 2h in a nitrogen atmosphere. After cooling to room temperature, the pre-carbonized product was repeatedly washed with deionized water until the pH was 2.5±0.5 and dried at 120°C. After cooling to room temperature, 400ml of potassium carbonate solution (20wt%) was added to the dried product, and stirred and soaked at 100°C for 4h, and filtered. The filtered product was then repeatedly washed with deionized water until the pH of the product was 11±0.5. 400 ml of nitric acid solution (10 wt%) was added to the obtained product, and stirred and soaked at 80 ° C for 4 h, and filtered. The filtered product was then repeatedly washed with deionized water until the pH of the product was 2.5 ± 0.5, and then dried at 120 ° C. The dried product was ball milled using a ball mill until the product D v 50 particle size is 6.0μm. Then the ball-milled product is carbonized at 1400℃ for 3h in an argon atmosphere and cooled naturally to room temperature to obtain the final product hard carbon. v 50The particle size is 5.4μm.
[0220] 2. Evaluation Example
[0221] 1.BET and aperture
[0222] Refer to GB / T 19587-2017 "Determination of Specific Surface Area of Solid Matter by Gas Adsorption BET Method" for testing. Put the hard carbon material (30-500 mg) into the sample tube and degas it. After degassing, turn off the heating power. After the sample cools to room temperature, backfill with helium and weigh the sample tube. Put the weighed sample tube into the BET specific surface area analyzer (Jingwei Gaobo JW-DX) and enter the sample mass into the analysis file. Click the instrument to start the adsorption and desorption test process. The results are automatically output after the test.
[0223] 2.D v 50 Particle Size Test Method
[0224] Use Malvern 3000 laser particle size analyzer for testing. Select carbon as the standard substance, detergent (Liby Fresh Lemon Detergent (Product Code 06920174736779)) plus water (volume ratio of detergent: water = 1:3) as a dispersant, set the following instrument test parameters: test time 10s, test number 3, shading 6-15%, stirring speed 2800r / min, ultrasonic mode on, power 50%. Click the laser particle size analyzer (Malvern 3000 laser particle size analyzer) to start the test, then add the primary sintering product or positive electrode material to the sample pool, control the amount added to adjust the sample pool shading to 6-15%. The instrument automatically repeats the test 3 times, and the average value of the 3 tests is taken as the mean of the test results.
[0225] 3.P content
[0226] Accurately weigh about 0.1g of hard carbon sample into a 50ml polytetrafluoroethylene digestion tube, add 5mL of 3:1 volume of concentrated hydrochloric acid (36-38wt%) and concentrated nitric acid (65-68wt%) to the weighed sample digestion tube, cover it and put it into a stainless steel reactor, place it in an oven and control the temperature to 180 degrees Celsius for about 10 hours, then stop heating and cool to room temperature. Transfer the cooled solution to a 50ml volumetric flask and finally make up to volume with ultrapure water. Prepare a single element P standard solution with 1% HNO 3 As the medium, 50mL of calibration standard samples with concentrations of 0, 5, 10, 20, and 50mg / L are prepared; the calibration sample is used to draw a calibration curve of the standard solution through the instrument ICP-OES (inductively coupled plasma emission spectrometer), and then the digested solution is tested in sequence. If it exceeds the upper limit of the curve (the detection limit is 0.001 weight %), it is diluted and tested again (the volume of the diluent used for dilution should be considered when calculating the P content). Finally, according to the measurement result of each sample, the concentration of the P element in the diluent of each sample is determined by referring to the calibration curve of the standard solution, and the final content of the P element is calculated in combination with the volume of the diluent to obtain the test result.
[0227] 4. Small-angle X-ray scattering
[0228] The Xenocs Xeuss 2.0 SAXS / WAXS test system was used, with a copper X-ray source of 30W (wavelength 0.1542nm) and an X-ray spot size of 0.8mm×0.8mm. The virtual detector mode of three combined images was used, and the sample-camera distance was adjusted to 0.55m. The corresponding scattering vector Q value was The measured intensity was calibrated for absolute intensity using glassy carbon as the standard sample, and the influence of all relevant factors (including sample thickness, air and sample holder scattering, etc.) was excluded. The two-dimensional scattering data (scattering intensity data within the 2θ angle (cone) range centered on the beam axis, with different colors representing different scattering intensities) was converted into a one-dimensional data curve (a set of data consisting of scattering vectors and corresponding scattering intensities) using Foxtrot 3.2.4 software. The one-dimensional data curve was fitted using SasView5.0.6 software to obtain d and ξ.
[0229] Disorder parameter f of hard carbon materials a The average pore diameter can be calculated by using the parameters d and ξ obtained by fitting the small-angle X-ray scattering data of hard carbon materials and substituting them into the following formula:
[0230]
[0231]
[0232]
[0233]
[0234] Some preparation conditions and physicochemical properties of the hard carbon materials of Examples 1-19 and Comparative Examples 1-7 are summarized in Table 1.
[0235] 5. Electrochemical performance test
[0236] Manufacturing of sodium-ion secondary batteries:
[0237] Button cell manufacturing: 0.45g hard carbon material, 0.025g SP (Swiss Special High Conductive Carbon Black SUPER-P) and 0.25g polyvinylidene fluoride (PVDF, PVDF5130 purchased from SOLVAY) glue (mass fraction 10%, solvent N-methylpyrrolidone (NMP)) were uniformly mixed, and then N-methylpyrrolidone was added to make a viscous glue. The glue was coated on aluminum foil (thickness 16μm), and then baked in a vacuum drying oven at 120℃ for 12h to obtain a negative electrode sheet (active material mass 4mg / cm 2 ). A metal sodium sheet (Aladdin) was used as the counter electrode (thickness 300±50μm). A glass fiber (Waterman) was used as the diaphragm (thickness 675μm). NaPF 6 The solution (the solvent is a mixture of EC and DMC, the volume ratio is EC / DMC=1:1) was used as the electrolyte, and 2032 button cells were assembled in an Ar atmosphere protection glove box.
[0238] Manufacturing of 26700 cylindrical battery cells (26mm in diameter, 70mm in height):
[0239] (1) Preparation of positive electrode sheet:
[0240] The layered oxides NaCu were mixed in a mass ratio of 96.5:1.5:1.5:0.5 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 O 2 , Super-P, PVDF and carbon nanotubes, and then uniformly dispersed in N-methyl-2-pyrrolidone (NMP) to obtain a positive electrode slurry; the positive electrode slurry was uniformly coated on both sides of an aluminum foil (thickness of 12 μm), and the single-sided surface density was 16.0 mg / cm 2 After drying and calendering (compacted density is 3.1mg / cm 3 ) and vacuum dried, and then welded with an ultrasonic welder an aluminum lead wire to obtain a positive electrode sheet.
[0241] (2) Preparation of negative electrode sheet:
[0242] The hard carbon material of the present invention, Super-P, SBR and CMC are mixed in a mass ratio of 94.5:1.5:2.5:1.5, and then uniformly dispersed in deionized water to obtain a negative electrode slurry; the negative electrode slurry is coated on both sides of a copper foil (thickness of 8 μm), and the single-side surface density is 9 mg / cm 2 (charge N / P ratio is 1.10), after drying and calendering (compacted density is 0.90mg / cm 3 ) and vacuum dried, and then welded with a nickel lead wire using an ultrasonic welder to obtain a negative electrode sheet.
[0243] (3) Preparation of battery cells:
[0244] A PE film with a thickness of 16 μm (12 μm for the separator, coated on both sides, 2 μm for each side) coated with ceramic on both sides is placed between the positive electrode and the negative electrode. Then, the sandwich structure consisting of the positive electrode, the negative electrode and the separator is wound, and the wound body is placed in a 26700 cylindrical battery steel shell, and then the electrolyte (by weight percentage, the composition is: 28% EC, 28% PC, 28% DEC, 12.5% NaPF 6 , 1% VC, 2% FEC, 0.5% PS; the injection coefficient is 4.0g / Ah), and the battery preparation is completed after assembly.
[0245] 5.1 Charge Gram Capacity
[0246] After the button cell is assembled, place the button cell at 25°C, discharge it to 0V at a constant current density of 20mA / g, let it stand for 10 minutes, then discharge it to 0V at a constant current density of 4mA / g, let it stand for 5 minutes; then charge it to 2.0V at a constant current density of 20mA / g, and record the charge capacity. Repeat the test three times according to the above method. Calculate the average of the charge capacity of the three tests, which is the charge capacity test result.
[0247] 5.2 First Coulombic Efficiency
[0248] After the button cell is assembled, place it at 25°C, discharge it at a constant current of 20mA / g to 0V, let it stand for 10 minutes, and then discharge it at a constant current of 4mA / g to 0V, and record the sum of the two discharge capacities as the first discharge capacity; then let it stand for 5 minutes, charge it at a constant current of 20mA / g to 2.0V, and record the charging capacity as the first charging capacity; the first charging capacity / first discharge capacity × 100% is the first coulombic efficiency.
[0249] 5.3 Cycle retention rate
[0250] At 25°C, charge the 26700 cylindrical battery cell at 1C constant current to 4.0V, then charge at constant voltage until the current is less than or equal to 0.1C, then let it stand for 10 minutes, and then discharge it at 1C constant current to 2.0V, then let it stand for 10 minutes. This is a charge and discharge cycle, and the discharge capacity is recorded as the discharge capacity of the first cycle of the battery. Perform 100 cycles of charge and discharge tests on the battery according to the above method, and record the discharge capacity of the 100th cycle. Then the discharge capacity of the 100th cycle / the discharge capacity of the first cycle × 100% is the cycle retention rate.
[0251] The electrochemical performance test results of the sodium ion secondary batteries made from the hard carbon materials of Examples 1-19 and Comparative Examples 1-7 are summarized in Table 2.
[0252]
[0253] Table 2 Electrochemical performance test results of sodium ion secondary batteries
[0254]
[0255] Combining Table 1 and Table 2, it can be seen that relative to the P content and f a Among the comparative examples CE1 to CE7, any one of which is not within the limited range, the embodiments E1 to E19 are generally significantly better in discharge gram capacity, first coulombic efficiency and cycle retention rate.
[0256] Comparing Examples E1 and E2 with Comparative Examples CE1 and CE3, it can be found that the main difference between them is that the P content in E1 and E2 is 0.026 wt% and 0.044 wt% respectively, while no P is detected in CE1 and the P content in CE3 is 0.310 wt%. E1 and E2 are significantly better than CE1 and CE3 in terms of the comprehensive performance of discharge gram capacity, first coulomb efficiency and cycle retention rate. A similar pattern can be found by comparing E1-E2 and CE4-CE5.
[0257] Comparing Examples E4 and E8 and Comparative Examples CE2 and CE6, it can be found that the difference between them is mainly that f a are 0.29 and 0.62 respectively, while in CE2 a is 0.20, f in CE6 a is 0.78, and E4 and E8 are significantly better than CE2 and CE6 in discharge gram capacity, first coulombic efficiency and cycle retention rate, respectively.
[0258] It can be seen that the present invention can regulate the content of P and f a Within a limited range, the discharge gram capacity, first coulombic efficiency and cycle retention rate of the negative electrode hard carbon material can be effectively improved.
[0259] The above is only an exemplary embodiment of the present invention. It should be noted that, for those skilled in the art, without departing from the inventive concept of the present invention, improvements can be made to the present invention, but these all belong to the protection scope of the present invention.
Claims
1. A negative electrode hard carbon material for a sodium ion secondary battery, which satisfies: The phosphorus content ranges from 0.001 wt % ≤ P ≤ 0.300 wt %, based on the total weight of the negative electrode hard carbon material; Unordered parameter f a The range is 0.25≤f a ≤0.75, where f a Calculated by the following formula: in Wherein d is the distance between two adjacent pores in the negative electrode hard carbon material. The average spacing of the calculation, ξ is the factor limiting the long-range orderly expansion. The correlation length, d and ξ of the negative electrode hard carbon material are obtained by fitting the small angle X-ray scattering data; wherein the average pore diameter of the negative electrode hard carbon material is 1.5-3.0 nm; and The BET specific surface area of the negative electrode hard carbon material is 1.0-35.0 m 2 / g. 2 . The negative electrode hard carbon material according to claim 1 , wherein the phosphorus content is in the range of 0.005 wt % ≤ P ≤ 0.250 wt %, based on the total weight of the negative electrode hard carbon material. 3 . The negative electrode hard carbon material according to claim 1 , wherein the phosphorus content is in the range of 0.010 wt % ≤ P ≤ 0.160 wt %, based on the total weight of the negative electrode hard carbon material. 4 . The negative electrode hard carbon material according to claim 1 , wherein the phosphorus content is in the range of 0.010 wt % ≤ P ≤ 0.100 wt % based on the total weight of the negative electrode hard carbon material.
5. The negative electrode hard carbon material according to claim 1, wherein 0.29≤f a ≤0.
50.
6. The negative electrode hard carbon material according to claim 1, wherein 0.33≤f a ≤0.
50.
7. The negative electrode hard carbon material according to claim 1, wherein 0.33≤f a ≤0.
46.
8. The negative electrode hard carbon material according to any one of claims 1 to 7, wherein the average pore diameter is 1.5 to 2.5 nm. 9 . The negative electrode hard carbon material according to claim 8 , wherein the average pore diameter is 1.7-2.3 nm.
10. The negative electrode hard carbon material according to any one of claims 1 to 7, wherein the BET specific surface area is 3.0 to 35.0 m 2 / g.
11. The negative electrode hard carbon material according to claim 10, wherein the BET specific surface area is 4.5-14.5 m 2 / g.
12. The negative electrode hard carbon material according to any one of claims 1 to 7, wherein the volume average particle size D of the negative electrode hard carbon material is v The range of 50 is 1.0-20.0μm.
13. The negative electrode hard carbon material according to claim 12, wherein the volume average particle size D v 50 ranges from 1.5-15.0μm.
14. A method for preparing the negative electrode hard carbon material according to any one of claims 1 to 13, comprising: (1) treating the carbon source in an air atmosphere at a treatment temperature of 60-300° C. for a treatment time of 1-24 hours; (2) adding a phosphorus source to the product obtained in step (1), and then treating the resulting mixture under an inert gas atmosphere at a treatment temperature of 60-300° C. for a treatment time of 1-12 hours; (3) pre-carbonizing the product obtained in step (2) at a pre-carbonization temperature of 400-650° C. for a pre-carbonization time of 0.5-12 hours under an inert gas atmosphere; (4) repeatedly washing the product obtained in step (3) with deionized water until the pH of the product is in the range of 2.0-5.0, and optionally drying; (5) uniformly mixing the product obtained in step (4) with at least one of sodium hydroxide, potassium hydroxide, sodium carbonate or potassium carbonate, sodium bicarbonate or potassium bicarbonate powder, and then sintering at a sintering temperature of 500-900° C. for a sintering time of 0.5-12 hours under an inert gas atmosphere; or The product obtained in step (4) is stirred and soaked in at least one of sodium hydroxide, potassium hydroxide, sodium carbonate or potassium carbonate, sodium bicarbonate or potassium bicarbonate solution at a temperature of 20-100° C. for 1-12 hours, and then filtered to obtain a filter cake; (6) repeatedly washing the product obtained in step (5) with deionized water until the pH of the product is in the range of 10.0-12.0; (7) soaking the product obtained in step (6) in an acid solution at a temperature of 20-100° C. for 1-12 h with stirring, then filtering, and repeatedly washing the filter cake with deionized water until the pH thereof is in the range of 2.0-5.0, and then drying; (8) crushing the product obtained in step (7) to D v 50 particle size in the range of 1.0-20.0 μm; and (9) The product obtained in step (8) is subjected to high temperature carbonization at a high temperature carbonization temperature of 1050-1600° C. for a high temperature carbonization time of 2-8 hours under an inert gas atmosphere, and is optionally crushed.
15. The method according to claim 14, wherein the treatment temperature in step (1) is 80-280°C.
16. The method according to claim 14, wherein the treatment time of step (1) is 2-20 hours.
17. The method according to claim 14, wherein the treatment temperature in step (2) is 60-260°C.
18. The method according to claim 14, wherein the treatment time of step (2) is 2-10 hours.
19. The method according to claim 14, wherein the pre-carbonization temperature in step (3) is 400-600°C.
20. The method according to claim 14, wherein the pre-carbonization time in step (3) is 1-8 hours.
21. The method according to claim 14, wherein the sintering temperature in step (5) is 550-850°C.
22. The method according to claim 14, wherein the sintering time in step (5) is 2-10 hours.
23. The method according to claim 14, wherein the high temperature carbonization temperature of step (9) is 1200-1500°C.
24. The method according to claim 14, wherein the high temperature carbonization time in step (9) is 2-6 hours.
25. The method according to any one of claims 14 to 24, wherein the carbon source is selected from one or more of coal, asphalt and biomass.
26. The method according to claim 25, wherein the coal is selected from one or more of bituminous coal and lignite.
27. The method according to claim 25, wherein the asphalt is selected from one or more of medium-temperature asphalt and high-temperature asphalt.
28. The method according to claim 25, wherein the biomass is selected from one or more of coconut shell, walnut shell, apricot shell, palm shell, lignin, cellulose, starch, bamboo.
29. The method according to any one of claims 14 to 24, wherein the phosphorus source is selected from one or more of phosphoric acid or phosphates.
30. The method according to claim 29, wherein the phosphorus source is selected from one or more of phosphoric acid, ammonium dihydrogen phosphate, sodium dihydrogen phosphate, and potassium dihydrogen phosphate.
31. The method according to claim 29, wherein the weight ratio of the product obtained in step (1) to the phosphorus element in the phosphorus source is 100:5 to 100:
45.
32. The method according to claim 29, wherein the weight ratio of the product obtained in step (1) to the phosphorus element in the phosphorus source is 100:5 to 100:
30.
33. The method according to claim 29, wherein when the phosphorus source is selected from one or more of phosphoric acid, ammonium dihydrogen phosphate, sodium dihydrogen phosphate, and potassium dihydrogen phosphate, the weight ratio of the product obtained in step (1) to the phosphorus source is 100:5 to 100:
100.
34. The method according to claim 29, wherein when the phosphorus source is selected from one or more of phosphoric acid, ammonium dihydrogen phosphate, sodium dihydrogen phosphate, and potassium dihydrogen phosphate, the weight ratio of the product obtained in step (1) to the phosphorus source is 100:30 to 100:
100.
35. The method according to any one of claims 14 to 24, wherein in step (5), one or more of the following conditions are met: Based on 100% by weight of the product obtained in step (4), the amount of sodium hydroxide, potassium hydroxide, sodium carbonate or potassium carbonate, sodium bicarbonate or potassium bicarbonate powder added on a dry weight basis is in the range of 5-50% by weight; and / or The concentration of the sodium hydroxide, potassium hydroxide, sodium carbonate or potassium carbonate, sodium bicarbonate or potassium bicarbonate solution is 0.5-40% by weight.
36. The method according to any one of claims 14 to 24, wherein in step (7), the concentration of the acid solution is 0.5 to 30 wt %; and / or The acid solution is selected from one or more of hydrochloric acid, sulfuric acid, nitric acid, hydrofluoric acid, citric acid and acetic acid.
37. A negative electrode composition for a sodium ion secondary battery, comprising the negative electrode hard carbon material according to any one of claims 1 to 13. 38 . A sodium ion secondary battery comprising the negative electrode composition for a sodium ion secondary battery according to claim 37 .
39. Use of the sodium ion secondary battery according to claim 38 in energy storage equipment for solar power generation, wind power generation, smart grid peak regulation, distributed power stations, backup power supplies or communication base stations.
Citation Information
Patent Citations
High capacity hard carbon materials comprising efficiency enhancers
CN105453305A
Hard carbon negative electrode material for lithium ion secondary battery and preparation method of hard carbon negative electrode material
CN113113601A
High-capacity hard carbon fast-charging negative electrode material as well as preparation method and application thereof
CN114695894A
Carbon negative electrode material and preparation method thereof, lithium ion battery negative electrode, lithium ion battery and electric equipment
CN115377414A